The efficacy and safety of intramuscular injections of methylcobalamin in patients with chronic nonspecific low back pain: a randomised controlled trial - Chiu, C.K.; Low, T.H.; Tey, Y.S.; Singh, Vivek Ajit; Shong, H.K. (2011)
Introduction: Chronic, nonspecific low back pain is a difficult ailment to treat and poses an economic burden in terms of medical expenses and productivity loss. The aim of this study was to determine the efficacy and safety of intramuscular metylcobalamin in the treatment of chronic nonspecific low back pain. Methods: This was a double-blinded, randomised, controlled experimental study. 60 patients were assigned to either the methylcobalamin group or the placebo group. The former received intramuscular injections of 500 mcg parenteral methylcobalamin in 1 ml solution three times a week for two weeks, and the placebo group received 1 ml normal saline. Patients were assessed with Oswestry Disability Index questionnaire Version 2.0 and Visual Analogue Scale pain score. They were scored before commencement of the injections and at two months interval. Results: Of the 60 patients, 27 received the placebo injections and 33 were given methylcobalamin injections. A total of 58 patients were available for review at two months (placebo: n is 26; methylcobalamin: n is 32). There was a significant improvement in the Oswestry Disability Index and Visual Analogue Scale pain scores in the methylcobalamin group as compared with the placebo group (p-value less than 0.05). Only minor adverse reactions such as pain and haematoma at the injection sites were reported by some patients. Conclusion: Intramuscular methylcobalamin is both an effective and safe method of treatment for patients with nonspecific low back pain, both singly or in combination with other forms of treatment.